2016
DOI: 10.1557/jmr.2016.282
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurements ofquasi-zero grain boundary energies in ceramics

Abstract: Nanocrystalline bulk materials (also called nanograined materials) are intrinsically unstable due to the excess grain boundary (GB) free energies. Dopants designed to segregate to boundaries have been proposed to lower excess GB energies, increasing stability against coarsening and enabling nanostructure features to survive high temperature processing and operational environments. It has been theoretically proposed that the GB energy of a material can eventually become zero as a function of dopant concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…In ionic solids, the segregation phenomenon was found to have a substantial effect on the electronic and catalytic properties, as well as on the sintering process. At certain level of impurity or on adding atoms, the segregation at the grain boundary may lower the surface or interfacial energy which may modify the defect concentration at the grain boundary and consequently modify the back‐to‐back Schottky barrier . Therefore, it seems reasonable to have a preferential electron path through the polycrystalline hematite sample.…”
Section: Discussionmentioning
confidence: 99%
“…In ionic solids, the segregation phenomenon was found to have a substantial effect on the electronic and catalytic properties, as well as on the sintering process. At certain level of impurity or on adding atoms, the segregation at the grain boundary may lower the surface or interfacial energy which may modify the defect concentration at the grain boundary and consequently modify the back‐to‐back Schottky barrier . Therefore, it seems reasonable to have a preferential electron path through the polycrystalline hematite sample.…”
Section: Discussionmentioning
confidence: 99%
“…grain boundary energies have shown that impurities may significantly lower the grain boundary energy of ceramics down to values below 0.025 J/m 2 [7]. While this may seem irrelevant front the exponential dependence of the grain boundary mobility, some impurities may have only minor effects on the activation energy and mobility, and thus the system will be mostly controlled by the thermodynamic aspect, as observed in Gd-doped yttria-stabilized zirconia discussed in the next session.…”
Section: Introductionmentioning
confidence: 89%
“…However, until recently, the grain boundary energy has not been considered a variable to design (meta)stable nanocrystalline ceramics. Following theoretical framework developed for the control of nanocrystalline metal alloys [25][26][27][28][29][30], a few papers have reported virtual stopping of grain growth of ceramics by introducing dopants targeting a reduction of the grain boundary energy [7,[31][32][33]. The grain boundary energy was lowered to essentially zero [7], signifying a negligible driving force for coarsening.…”
Section: Thermodynamics Of Grain Growthmentioning
confidence: 99%
“…To solve the poor thermal stability of NC materials, many ways, including the introduction of foreign solute atoms, the precipitation of second particles, etc., have been attempted through using the methods of theoretical models, experimental techniques and computer simulations. These investigations can be commonly classified into two categories, that is, the thermodynamic stabilization arising from reduced GB energy [20][21][22][23][24][25][26] and the kinetic stabilization due to the decreased GB mobility [27][28][29][30] (or the increased activation energy for GB migration). Table 1 summarizes the representative review articles and their foci.…”
Section: Introductionmentioning
confidence: 99%